Tra Rosario e Buenos Aires: Il Teatro Municipale Rafael de Aguiar di San Nicolás de los Arroyos (1905-1908) - Murace, Giulia (2021)
This paper analyzes the historical-artistic aspects of the Teatro Muncipal in San Nicolás de los Arroyos (Buenos Aires), inaugurated on August 10, 1908 and the imaginary it contributed to build in a provincial city at the beginnings of 1900. In Argentina, by the end of the 19th century and the beginning of the 20th, several opera houses appeared, in both large cities and small urban centers. Some peculiarities of this theater lead us to highlight alternative routes of artistic circulation, where Buenos Aires is not always the center and where local intermediaries have had preeminence; since a greater dialogue with the city of Rosario than with the nation´s capital was established.